Qué saben, qué hacen y cuál es la participación de los líderes en la prevención del dengue. El caso del barrio Floralia de Santiago de Cali - Maldonado-Gómez, María Cristina; García-Moreno, Patricia; Méndez-Paz, Fabián (Prospectiva. Revista de Trabajo Social e Intervención Social, 2009)
In this article, knowledgments and practices of dengue disease of the inhabitants of Floralia, a neighbourhood of Cali-Colombia, are analysed through the perceptions of their colective leaders. Interpretation of the results were analysed using cualitative procedures for social investigations. This method facilitates the understanding of the inhabitants perceptions about the dengue disease, with the porpouse of designing an ecohealth procedure, that icludes investigation strategies with interdiciplinary and interinstitutional actions. Results exposed in this manuscript are part of the proyect entitled " Design, implementation and evaluation of an intervention strategy on dengue with an ecohealth approach in a demostrative area of the urban Cali" (Méndez and Mosquera, 2005), made by the Epidemology and Population Health Group of the Universidad del Valle. Dengue is a disease know by the leaders of Floralia, but their perceptions on it are confusing, do not include the posibility of a epidemy and they believe they do actions to prevent and to atend the syntoms asosiated to the disease. knoledgements and practices are ambigous beacuse they mix up informaly learned traditional practices with information brought by biological, medicinal and ecological investigations. The cultural syncretism of this urban population of scare socioeconomic resources is apreciated, in a multicultural city wiht segemnted problems of development and with a wide socioeconomic differentiation. The knowledgments and practices of the leaders on the dease nature, transmittion, breeding, prevention, syntoms and treatment are exposed in this article. Furthermore, an analysis of the type of communitary partcipation is exposed, which enables to visualize intervention strategys on dengue.